The importance of smell and taste in everyday life: dysfunction in COVID-19 patients - Stanojlović, Olivera (Medicinski podmladak, 2021)
Human-to-human transmission of coronavirus (SARS-CoV-2), COVID-19 (coronavirus disease 2019), is characterized by a pandemic exponential rate and the patients with mild to moderate infection have odor and taste problems that represent a new atypical disease. A new viral syndrome of acute anosmia or “new loss of taste or smell” without rhinitis and nasal obstruction or rhinorrhea has been placed on the list of symptoms that may occur 2 to 14 days after exposure to the COVID-19 virus. Two months after declaring the COVID-19 pandemic in May 2020, the World Health Organization (WHO) has recognized changes in the perception of smell and taste as symptoms of this disease. The described cardinal symptoms are more common in the population of young patients and able-bodied people which facilitates the spread of disease. Significantly higher prevalence of patients with COVID-19 who have lost their taste and smell is treated at home (rare hospitalization), lung damage is rare, as well as oxygen therapy with mild lymphopenia. Different scenarios of SARS-CoV-2 viral infection can be assumed: it is probable that the virus does not enter directly into olfactory sensory neurons (they do not have ACE2 and TMPRSS2 receptors), but it is localized to vascular pericytes and causes inflammatory processes and vasculopathies. On the other hand, direct infection of non-neuronal cells which contain said receptors is possible. Those are specific cell types in the olfactory epithelium such as sustentacular, horizontal basal cells as well as Bowman's glands which leads to massive degeneration and loss of olfactory neurons. The sense of taste is a complex sensation that is the result of the interaction of smell, taste, temperature and texture of food. The virus damages cranial nerves, epithelial receptors and blood vessels, leading to taste damage (ageusia or dysgeusia).            A multidisciplinary approach with epidemiological, clinical and basic research is needed to elucidate the mechanism of sensorineural odor and taste loss caused by coronavirus.
Keywords: SARS-CoV-2; anosmia; ageusia; ACE2